On perturbed Szego recurrences - Castillo, Kenier (Elsevier B.V., 2014)
The purpose of the present contribution is to investigate the effects of finite modifications of Verblunsky coefficients on Szego recurrences. More precisely, we study the structural relations and the corresponding C-functions of the orthogonal polynomials with respect to these modifications from the initial ones. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Three term recurrence relation; Orthogonal polynomials on the real line; Szego recurrences; Orthogonal polynomials on the unit circle; Perturbed Verblunsky coefficients